2011
DOI: 10.1021/ja2013664
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of a Rhenium Bipyridyl CO2 Reduction Catalyst to Rutile TiO2

Abstract: We have characterized the covalent binding of the CO(2) reduction electrocatalyst ReC0A (Re(CO)(3)Cl(dcbpy) (dcbpy =4,4'-dicarboxy-2,2'-bipyridine)) to the TiO(2) rutile (001) surface. The analysis based on sum frequency generation (SFG) spectroscopy and density functional theory (DFT) calculations indicates that ReC0A binds to TiO(2) through the carboxylate groups in bidentate or tridentate linkage motifs. The adsorbed complex has the dcbpy moiety nearly perpendicular to the TiO(2) surface and the Re exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(174 citation statements)
references
References 36 publications
9
165
0
Order By: Relevance
“…Batista, Lian, and co-workers have determined the vibrational spectra of carboxylate-bound rhenium bipyridine catalysts on (001) TiO 2 single-crystal surfaces using calculations to study their conformations, but did no CO 2 reduction studies. 197 210 Yields as high as 400 ppm of CO g −1 h −1 were achieved in the first 30 min of the reaction using small amounts of RuO x as a co-catalyst and Na 2 SO 3 as a sacrificial hole scavenger. However, the yields quickly decayed within the first hour.…”
Section: +mentioning
confidence: 99%
“…Batista, Lian, and co-workers have determined the vibrational spectra of carboxylate-bound rhenium bipyridine catalysts on (001) TiO 2 single-crystal surfaces using calculations to study their conformations, but did no CO 2 reduction studies. 197 210 Yields as high as 400 ppm of CO g −1 h −1 were achieved in the first 30 min of the reaction using small amounts of RuO x as a co-catalyst and Na 2 SO 3 as a sacrificial hole scavenger. However, the yields quickly decayed within the first hour.…”
Section: +mentioning
confidence: 99%
“…Re-based dyes have been extensively studied over the last 10 years as model systems for charge injection into TiO 2 and other semiconductors. 12,[32][33][34][35][36] From a comparison to density functional theory (DFT) calculations of the frequencies, we concluded that the dyes attached to the TiO 2 as either monomers or aggregates of two or three molecules, because the coupling between metal carbonyl groups is large enough to excitonically delocalize the vibrations across multiple carbonyl groups on adjacent molecules. 31 An illustration of FIG.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[10][11][12][13][14][15][16][17] Ta king into account the effective charge-separation processes for water splitting/CO 2 reduction as well as issues associated with separation of the products, at andemP EC device with separated electrodes to perform differenthalf-reactions becomes more favorable. [3,[10][11][12][13][14][15][16][17] Ta king into account the effective charge-separation processes for water splitting/CO 2 reduction as well as issues associated with separation of the products, at andemP EC device with separated electrodes to perform differenthalf-reactions becomes more favorable.…”
Section: Introductionmentioning
confidence: 99%